2011
DOI: 10.1002/mds.23774
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal storage disorders and Parkinson's disease: Gaucher disease and beyond

Abstract: Parkinson's disease is associated with mutations in the glucocerebrosidase gene, which result in the enzyme deficiency causing Gaucher disease, the most common lysosomal storage disorder. We have performed an exhaustive literature search and found that additional lysosomal storage disorders might be associated with Parkinson's disease, based on case reports, the appearance of pathological features such as α-synuclein deposits in the brain, and substantia nigra pathology. Our findings suggest that the search fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
105
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 156 publications
(212 reference statements)
3
105
0
3
Order By: Relevance
“…Loss-of-function mutations in metabolic genes have recently been recognized as important risk factors for common neurodegenerative disorders such as Parkinson's and Alzheimer's disease (23,24). A well-established example of this is the relationship between GD and PD, where mutations in GBA1 lead to increased risk for PD (6).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations in metabolic genes have recently been recognized as important risk factors for common neurodegenerative disorders such as Parkinson's and Alzheimer's disease (23,24). A well-established example of this is the relationship between GD and PD, where mutations in GBA1 lead to increased risk for PD (6).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Deficiency of GBA1 forms the basis for the most common inherited lysosomal storage disorder, Gaucher disease. [2] Recently, mutations of GBA1 have been reported to markedly increase the risk for Parkinsonism, [7][8][9] and excessive degradation of glucosylceramide by GBA2 may play a role in neuropathology. [4,[10][11][12] The cytosolic broadspecificity b-glucosidase (GBA3) is thought to be involved in degrading xenobiotic b-glucosides.…”
mentioning
confidence: 99%
“…In these diseases, a defi ciency of hexosaminidase A and/or B leads to a buildup of GM2 that leads to neurodegeneration. Both diseases are associated with development of Lewy bodies and synuclein aggregates ( 7,8 ). As in the case of GlcCer, GM2 also has been shown to interact with synuclein and may contribute to neurodegeneration via a similar feedback loop, as proposed for glucocerebrosidase and synuclein ( 49,50 ).…”
Section: Approaches To Therapeutic Interventionmentioning
confidence: 86%
“…In NPC disease, a defect in the cholesterol transporters, NPC1 or NPC2, leads to lysosomal accumulation of cholesterol, GlcCer, and downstream glycosphingolipids ( 38,39 ), along with accumulation of synuclein in brain tissue ( 7,8 ). Recent studies have suggested that, as with GBA mutations, patients heterozygous for mutations in NPC1 may develop PD ( 40 ).…”
Section: Approaches To Therapeutic Interventionmentioning
confidence: 99%
See 1 more Smart Citation